Identificación cromatográfica de Benzoilecgonina en orina de personas detenidas en el Complejo Policial de Trujillo, enero –marzo 2018 - Neira Casana, Carlos Ivan (2019)
This report was oriented to the Benzoilecgonina Chromatographic Identification in people detained in the Trujillo Police Complex, January - March 2018. Benzoylecgonine was determined quantitatively in 548 urine samples, collecting approximately 50 mL of urine in the weighing area of said dependence police, was processed by thin layer chromatography (TLC), using as a standard a chloroform solution of basic cocaine paste (PBC). Once the run in the chromatoplate was performed, it was revealed with the modified Dragendorff reagent. It was found that 13% of urine samples from detainees had a positive result, of these 40% corresponds to the District of Hope, 60% corresponds to people aged between 18 and 30 years and 97% corresponds to the male sex